Effect of steroids on the activation status of platelets in patients with Immune thrombocytopenia (ITP). (11th March 2014) - Bhoria, Preeti; Sharma, Saniya; Varma, Neelam; Malhotra, Pankaj; Varma, Subhash; Luthra-Guptasarma, Manni
Abstract: The activation status of platelets in Immune Thrombocytopenia (ITP) patients – which is still somewhat controversial – is of potential interest, because activated platelets tend to aggregate (leading to excessive clotting or thromboembolic events) but cannot do so when platelet numbers are low, as in ITP. Although corticosteroids are the first line of therapy in ITP, the effect of steroids on activation of platelets has not been evaluated so far. We examined the status of platelet activation (with and without stimulation with ADP) in ITP patients, at the start of therapy (pre-steroid treatment, naive) and post-steroid treatment (classified on the basis of steroid responsiveness). We used flow cytometry to evaluate the levels of expression of P-selectin, and PAC-1 binding to platelets of 55 ITP patients and a similar number of healthy controls, treated with and without ADP. We found that platelets in ITP patients exist in an activated state. In patients who are responsive to steroids, the treatment reverses this situation. Also, the fold activation of platelets upon treatment with ADP is more in healthy controls than in ITP patients; treatment with steroids causes platelets in steroid-responsive patients to become more responsive to ADP-activation, similar to healthy controls. Thus steroids may cause changes in the ability of platelets to get activated with an agonist like ADP. Our results provide new insights into how, and why, steroid therapy helps in the treatment of ITP.